2013
DOI: 10.1039/c3cs35524a
|View full text |Cite
|
Sign up to set email alerts
|

Structural disorder in molecular framework materials

Abstract: It is increasingly apparent that many important classes of molecular framework material exhibit a variety of interesting and useful types of structural disorder. This tutorial review summarises a number of recent efforts to understand better both the complex microscopic nature of this disorder and also how it might be implicated in useful functionalities of these materials. We draw on a number of topical examples including topologically-disordered zeolitic imidazolate frameworks (ZIFs), porous aromatic framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 57 publications
2
109
0
4
Order By: Relevance
“…Internal surface defects may be static or dynamic (Cairns and Goodwin, 2013). Dynamic effects, cf., ligand rotation, will be disregarded as they are not formed upon or affected by SALE.…”
Section: Resultsmentioning
confidence: 99%
“…Internal surface defects may be static or dynamic (Cairns and Goodwin, 2013). Dynamic effects, cf., ligand rotation, will be disregarded as they are not formed upon or affected by SALE.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, such models could provide chemists with a tool to assist them in the design and synthesis of new NTE materials which, for example, could be built as MOFs [59,60], metal cyanides [61,62] or ceramics [63,64], and optimized so as to achieve some desired thermal expansion property. The applicability or the model presented here to real systems depends to a significant degree on the validity of the assumptions made.…”
Section: Resultsmentioning
confidence: 99%
“…76 By high-resolution neutron diffraction it was shown that UiO-66(Zr) framework contains a significant amount of vacancies due to the missing ligands. 77 The concentration of vacancies can be tuned by using the acetic acid modulator and thus manipulate the porosity properties of the MOF.…”
Section: Structure Defects and Framework Voidsmentioning
confidence: 99%